Incorporation of Wheat Bran in Broilers Diets - Ali, M.N.; Sekken, M.S. Abou; Mostafa, Kout El-Kloub M. El. (International Journal of Poultry Science, 2007)
A total number of 360 day old male Ross broiler chicks were randomly assigned into eight experimental treatment groups (45 each) to study the effect of incorporated 30% wheat bran (WB) in broiler diets and the possibility to improve the feeding value of WB when supplemented with some feed additives. In Treatment 1 birds received control diet and birds in treatment 2 received the basal wheat bran diet (WB-diet). Birds of treatment 3,4,5,6,7 and 8 received the WB-diet supplemented with 0.01% Xylam (E), E +1% Radish extract (RE), 1% Tomato extract (TE), 1%TE +1%RE, 1% Sodium Sulphate (SS) and 1% SS +1% TE. Results showed that there were insignificant differences in weight gain (WG) and feed conversion (FC) between birds fed control diet and WB-diet in all growth periods. In the finisher period, there were insignificant differences among all treatments in WG and FC. The feed additives used failed to improve performance of WB-diet group under the conditions of this study. The WB-diet without or with additives significantly decreased abdominal fat % compared to the control diet. Addition of TE+RE to WB-diet improved the digestibility of all nutrients. WB-diet alone or with E significantly increased plasma antioxidant capacity while it decreased total plasma cholesterol compared to the control diet. The addition of TE alone or with RE to WB-diet significantly increased the level of plasma calcium. The WB-diet alone or with either E+RE or TE significantly increased globulin level in plasma compared to the control diet. It could be concluded that not only 30% WB can be incorporate into broiler diets without adverse effect on performance but also it have a beneficial effect on plasma antioxidant capacity, phosphorus and globulin.